Resiliensi Sosial Nelayan Terhadap Kecelakaan Laut di Pelawangan Puger Kabupaten Jember - Koko Komarudin; Retno Adrianti; Mustain Mashud (The Journal of Society and Media, 2022)
Sea accident often occurs in Puger every year. It does not make Puger’s fishermen give up, they are able to survive and increase in number. This study aims to reveal the hidden veil behind the social resilience to sea accidents by analyzing communication network and the sociocultural of the fishing community. The research uses a phenomenological approach. This study shows that the fishermen build communication networks through cellphones and radio communication community to exchange information on important events at sea. They also keep local wisdom activities consist of Petik Laut, recitation congregation and client patron’s relationship. Petik Laut and recitation congregation vertically interpreted to increase their belief in God Almighty providing safety and horizontally increasing solidarity, building mutual awareness of helping each other in difficulties and strengthening the patron client structure to overcome financial problems as a result of sea accidents. Therefore, social media and local wisdoms reinforce social resilience.